Appendiceal Diverticulitis in a Young Female Diagnosed on Pathology after Laparoscopic Appendectomy for Acute Appendicitis - Oluwatobi O. Onafowokan; Aboubakr Khairat; Hugo J. R. Bonatti (Case Reports in Medicine)
Background. Appendiceal diverticulitis is a rare cause of inflammation of the appendix, which may mimic acute appendicitis. Its diagnosis is often delayed, and its occurrence carries an increased risk of significant complications, such as perforation. Case Presentation. A 23-year-old woman presented with sudden onset, severe, right lower quadrant abdominal pain and nausea. Her WBC was elevated, and abdominal CT showed findings indicative of acute appendicitis with a 13 mm fluid-filled appendix and local stranding. During laparoscopic appendectomy, significant inflammation was found around the appendix with some mucous material around the tip. The appendix base was not involved, and an endoloop was used to secure the stump. No other intra-abdominal abnormalities were observed. The patient recovered uneventfully. Pathology showed no classic appendicitis but appendiceal diverticulitis with signs of perforation. Discussion. Appendiceal diverticulitis is a rare condition which cannot be distinguished from acute appendicits clinically and on imaging. Diagnosis may be established based on pathology such as in our case. Appendectomy is indicated in appendiceal diverticulitis, and an appendix diverticulum is incidentally found during surgery or other investigations. This is due to the increased risk of perforation and the reported development of malignant tumors, including the appendix carcinoid.